2011
DOI: 10.1007/s00330-011-2168-5
|View full text |Cite
|
Sign up to set email alerts
|

An education and training programme for radiological institutes: impact on the reduction of the CT radiation dose

Abstract: Objectives To establish an education and training programme for the reduction of CT radiation doses and to assess this programme's efficacy. Methods Ten radiological institutes were counselled. The optimisation programme included a small group workshop and a lecture on radiation dose reduction strategies. The radiation dose used for five CT protocols (paranasal sinuses, brain, chest, pulmonary angiography and abdomen) was assessed using the dose-length product (DLP) before and after the optimisation programme.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 45 publications
2
11
0
2
Order By: Relevance
“…They published also a radiation dose reduction while preserving diagnostic image quality in pediatric head CT examinations, after a radiologic staff training [27]. Schindera et al reported the same effect for adult paranasal sinuses, brain, chest, pulmonary arteries, and abdomen CTs [24]. The authors reported that the largest decrease in radiation dose was reached for paranasal sinus and pulmonary arteries scans.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…They published also a radiation dose reduction while preserving diagnostic image quality in pediatric head CT examinations, after a radiologic staff training [27]. Schindera et al reported the same effect for adult paranasal sinuses, brain, chest, pulmonary arteries, and abdomen CTs [24]. The authors reported that the largest decrease in radiation dose was reached for paranasal sinus and pulmonary arteries scans.…”
Section: Discussionmentioning
confidence: 90%
“…No significant dose reduction for abdominal CTs was found; suboptimal image quality for low-contrast lesions in abdominal CTs was most likely identified as the reason. Education and training programs for radiological institutes was concluded to be effective in achieving substantial reduction in CT dose [24]. Sheyn et al reported that staff radiation safety education can improve radiation safety practices in pediatric interventional radiology, and thus, decrease exposure to radiation for both staff and patients [22].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Praksa je pokazala da su ustanove koje su uvele dose management software bile u mogućnosti smanjiti prosječnu efektivnu dozu po CT proceduri za 25-30% [15]. Smanjenjem prosječne efektivne doze i posljedičnim smanjenjem rizika po pacijenta mogu se prevenirati posljedice u smislu razvoja velikog broja malignih bolesti te postići značajne uštede u zdravstvenom sustavu koje daleko prevazilaze cijenu instalacije dose management software-a.…”
Section: Zaključciunclassified
“…They should also verify the indication of the dose indicators (CTDI vol , DLP, and dose efficiency parameters) and check if the standard protocols are compatible with the recommended DRL. They should also promote staff coaching in order to increase awareness levels in terms of the dose problematic [60,61]. Medical physicists should clearly explain the impact of the size of the patient on his/her exposure.…”
Section: Role Of Medical Physicistsmentioning
confidence: 99%